Paracoccidioides lutzii Infects Galleria mellonella Employing Formamidase as a Virulence Factor. - Elisa Dias Pereira; Thalison Rodrigues Moreira; Vanessa Rafaela Milhomem Cruz-Leite; Mariana Vieira Tomazett; Lana O'Hara Souza Silva; Daniel Graziani; Juliana Assis Martins; André Corrêa Amaral; Simone Schneider Weber; Juliana Alves Parente-Rocha; Célia Maria de Almeida Soares; Clayton Luiz Borges (Public Library of Science (PLoS), 2024)
The formamidase (FMD) enzyme plays an important role in fungal thriving by releasing a secondary nitrogen source as a product of its activity. In Paracoccidioides species, previous studies have demonstrated the upregulation of this enzyme in a wide range of starvation and infective-like conditions. However, Paracoccidioides lutzii formamidase has not yet been defined as a virulence factor. Here, by employing in vivo infections using an fmd-silenced strain in Galleria mellonella larvae model, we demonstrate the influence of formamidase in P. lutzii's immune stimulation and pathogenicity. The formamidase silencing resulted in improper arrangement of the nodules, poor melanogenesis and decreased fungal burden. Thus, we suggest that formamidase may be a piece composing the process of molecular recognition by Galleria immune cells. Furthermore, formamidase silencing doubled the observed survival rate of the larvae, demonstrating its importance in fungal virulence in vivo. Therefore, our findings indicate that formamidase contributes to Galleria's immune incitement and establishes the role of this enzyme as a P. lutzii virulence factor.